THE EFFECT OF ENTREPRENEURIAL LEADERSHIP ON ORGANIZATIONAL PERFORMANCE: LITERATURE REVIEW - Herlina, Erna; Tukiran, Martinus; Anwar, Syaiful (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2021)
In a competitive, dynamic, complex and uncertain business environment as it is today, a leadership type is needed that can play an important role for the survival, success, and growth of the organization. This paper aims to review the influence of entrepreneurial leadership on organizational performance in terms of three hierarchies: individuals, groups/teams, and the organization as a whole. According to the findings of the review, entrepreneurial leadership has a major impact on the individual performance of employees and teams, especially in terms of creativity and creative behavior. Moreover, Entrepreneurial leadership has a significant effect on overall organizational performance both in financial and non-financial dimensions.